Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1038/s41598-022-15242-2
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of cancer-related developmentally regulated GTP-binding protein 1 (DRG1) is conserved between sponges and humans

Abstract: Cancer is a disease caused by errors within the multicellular system and it represents a major health issue in multicellular organisms. Although cancer research has advanced substantially, new approaches focusing on fundamental aspects of cancer origin and mechanisms of spreading are necessary. Comparative genomic studies have shown that most genes linked to human cancer emerged during the early evolution of Metazoa. Thus, basal animals without true tissues and organs, such as sponges (Porifera), might be an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 69 publications
(124 reference statements)
1
9
0
Order By: Relevance
“…DRG1 is an evolutionary conserved GTPase that has been implicated in various tumors, but its role in cancer is not yet fully understood. Our study [ 73 ], as well as other studies, confirmed the localization of DRG1 in the cytosol of various cell lines (MCF-7 and HeLa human cancer cell lines, mouse 3T3 cells, and Drosophila melanogaster cells) [ 94 , 95 , 96 ].…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…DRG1 is an evolutionary conserved GTPase that has been implicated in various tumors, but its role in cancer is not yet fully understood. Our study [ 73 ], as well as other studies, confirmed the localization of DRG1 in the cytosol of various cell lines (MCF-7 and HeLa human cancer cell lines, mouse 3T3 cells, and Drosophila melanogaster cells) [ 94 , 95 , 96 ].…”
Section: Resultssupporting
confidence: 87%
“…The developmentally regulated GTP-binding protein (DRG) subfamily consists of two paralogs, DRG1 and DRG2. Both are involved in protein translation [ 91 ], microtubule regulation [ 92 ], and cell proliferation [ 73 , 93 ]. DRG1 is an evolutionary conserved GTPase that has been implicated in various tumors, but its role in cancer is not yet fully understood.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations